Hubungan Pola Makan dan Aktivitas Fisik dengan Kejadian Obesitas pada Pra Lansia di Desa Sukawijaya Wilayah Puskesmas Tambelang - Ika Fauziyah; Siti Arifah; Aprilina Sartika (Malahayati Nursing Journal, 2026)
ABSTRACT Obesity is a health problem caused by energy imbalance due to unhealthy diet and lack of physical activity. The prevalence of obesity in the pre-elderly group (aged 45-59 years) in Sukawijaya Village, Tambelang Health Center Area, is quite high, namely 72 pre- elderly. The prevalence of overweight and obesity in Bekasi City reached 17.41%, while in Bekasi Regency the figure was 10.17% (Ministry of Health, 2019). Obesity in pre elderly can increase the riskof non-communicable diseases such as diabetes, hypertension, heart disease.  This study aims to determine therelationship between diet and physical activity with the incidence of obesity in pre-elderly people in Sukawijaya Village. The research design used was cross-sectional with total sampling, involving 72 respondents. Obesity status was determined based on Body Mass Index (BMI), diet was measured using a questionnaire about the type, frequency, and amount of food, while physical activity was measured using the International Physical Activity Questionnaire (IPAQ). Data analysis was performed using the Chi-Square test. Results: The results showed a significant relationship between diet and obesity (p-value 0.002) and physical activity with obesity (p-value 0.011). Conclusion: The results indicate a relationship between diet and physical activity with the incidence of obesity in pre-elderly people in Sukawijaya Village. Suggestion: Pre-elderly people in Sukawijaya Village are advised to implement a healthy dietwith balanced nutritious foods and high fiber, and increase physical activity through light exercise such as walking or gymnastics to maintain energy balance and prevent obesity. Keywords: Dietary Patterns, Physical Activity, Obesity, Pre-Elderly.  ABSTRAK Obesitas merupakan masalah kesehatan yang disebabkan oleh ketidakseimbangan energi akibat pola makan yang tidak sehat dan kurangnya aktivitas fisik. Prevalensi obesitas pada kelompok pra lansia (usia 45-59 tahun) di DesaSukawijaya Wilayah Puskesmas Tambelang, cukup tinggi yaitu sebanyak 72 pra lansia. Prevalensi kelebihan berat badan dan obesitas di Kota Bekasi mencapai 17,41%, sementara di Kabupaten Bekasi angkanya sebesar 10,17% (Kemenkes, 2019). Obesitas pada pra lansia dapat meningkatkan risiko penyakit tidak menular seperti diabetes, hipertensi, penyakit jantung. Penelitian ini bertujuan untuk mengetahui hubungan antara pola makan dan aktivitas fisik dengan kejadian obesitas pada pra lansia di Desa Sukawijaya. Desain penelitian yang digunakan adalah cross-sectional dengan total sampling, melibatkan 72 responden. Status obesitas ditentukan berdasarkan Indeks Massa Tubuh (IMT), pola makan diukur menggunakan kuesioner tentang jenis, frekuensi, dan jumlah makan, sedangkan aktivitas fisik diukur menggunakan International Physical Activity Questionnaire (IPAQ). Analisis data dilakukan menggunakan uji Chi-Square. Hasil penelitian menunjukkan adanya hubungan signifikan antara pola makan dengan obesitas (p-value 0,002) dan aktivitas fisik dengan obesitas (p-value 0,011). Hasil menujukan adanya hubungan pola makan dan aktivitas fisik dengan kejadian obesitas pada pra lansia di Desa Sukawijaya. Kata Kunci: Pola Makan, Aktivitas Fisik, Obesitas, Pra Lansia.